(3QSGdI aj CfhGY GdRGjQLGJs - (3EHQGgje GafOjs
(3ChdgG (B:s
(3eaJGM SQ GdbWH GdbW MQhag hJLeYge HGddbW dSQ jfLdG jdhM SfGgG YfO dbW MQhagG ceG dGM HQb aj OLi Gddjd hGfLdG s
(3BNQgG (B:s
(3hQCjfG SGYGJ OQL GdWGdY jRf hPGdc aj YQV dg VQHfG GdSHYI YTQ OQLI hNeSjf ObjbI bj GKfGA YTQ acGf GdMGUd (B7 s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs